Тнe deformation of left ventricular walls in aneurism and arterial hypertension - M. М. Moroz; V. V. Lazоryshinetz; A. V. Rudenko; V. I. Ursulenko; О. M. Trembovetskaya; О. V. Juvchik (Ukrainian Journal of Cardiovascular Surgery, 2017)
Arterial hypertension (AH) is a frequent concomitant diagnosis in patients with postinfarction left ventricular (LV) aneurysm.Objective: to investigate the effect of hypertension on the deformation of the walls of LV in patients with postinfarction aneurysm.Patients (63) of the «National Institute of Сardio -Vascular Surgery» in the period from 2012 – 2016 with a diagnosis of aneurysm LV were investigated. The parameters of the deformation of the stems LV have been determined. Due to vectoring echocardiography the tendencies of enlargement curvature of LV the tendencies of the decline of the longitudinel deformation were detected.